Learning to Love Math: Teaching Strategies That Change Student Attitudes and Get Results - Willis, Judy (Association for Supervision & Curriculum Development, 2010)
A book that explains how negative attitudes toward math get established in the brain and what teachers can do to turn those attitudes around. Includes more than 50 strategies (suitable for any grade level) that give students a math attitude makeover, reduce mistake anxiety, and relate math to students' interests and goals.